EGFR and HER2neu Expression in Gall Bladder Carcinoma and Its Association with Clinicopathological Parameters - An Institutional Experience from North India - Abeer, Inara; Khan, Sabina; Hasan, Mohd. Jaseem; Hussain, Musharraf (Asian Pacific Journal of Cancer Biology, 2021)
Objective: Gallbladder cancer (GBC) is the most common biliary tract malignancy found worldwide with very high incidence in North India especially Delhi region. It is characterized by poor prognosis and ineffective treatment especially in advanced stage. The aim of this study was to evaluate EGFR and HER2/neu immunoexpression in cancer patients and to correlate it with the clinicopathological parameters so as to identify GBC patients who can benefit from targeted therapy. Methods: Present study was conducted in the Department of Pathology, Hamdard Institute of Medical Sciences & Research, New Delhi. A total of 40 cases of Gallbladder carcinoma (GBC) were evaluated for Immunohistochemical expression of EGFR and HER2/neu. Clinicopathological parameters of GBC were studied and correlated with immunoexpression of EGFR and HER2 /neu. Result: The mean age of the GBC patients was 55.9 years with 90% being females. On histopathology, 34(85%) cases were conventional adenocarcinoma. The EGFR expression was positive in 29/40 cases (72.5%). It was significantly more positive in poorly differentiated grade and advanced stages of gall bladder carcinoma (P<0.05). The expression of HER2/neu was positive in 13/40 cases (32.5%). It was significantly more positive in well differentiated gall bladder carcinoma (P<0.05). Immunoexpression of EGFR was inversely related with HER2/neu expression and this association was statistically significant. Conclusion: Among GBC patients, EGFR expression and HER2/neu expression was 72.5% and 32.5%, respectively. Significant EGFR expression was seen in poorly differentiated and advanced stage cancers while significant HER2/neu expression was seen in well differentiated gall bladder carcinomas. To conclude, these two markers HER2/neu and EGFR can be used as predictive and prognostic markers respectively, with rationale to further explore the use of anti-HER2 and anti- EGFR therapy in gall bladder cancer.